1988
DOI: 10.1016/0014-5793(88)81357-7
|View full text |Cite
|
Sign up to set email alerts
|

Subunit‐specific phosphorylation of pyruvate kinase in medullary thyroid carcinomas of the rat

Abstract: Pyruvate kinase from anaplastic medullary thyroid carcinomas contains predominantly K-type subunits, whereas pyruvate kinase from differentiated medullary thyroid carcinomas consist of M-and K-type subunits in about equal proportion. In order to analyse the incorporation of phosphate in the respective isozymes after endogenous phosphorylation of cytosolic extracts with [a2P]ATP, homotetrameric isozymes as well as heterotetrameric hybrids of differentiated tumors were resolved by affinity chromatography on Blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…An example that supports this hypothesis is the observation that solid tumors (which are hyperproliferative, usually hypoxic, and highly dependent on glycolysis) re-express the fetal M 2 isozyme of PK in addition to an increased expression of all glycolytic enzymes and lactate dehydrogenase ( ). This phenomena has been particularly well-documented for human neuroectodermal (brain) tumors () and breast tumors ().…”
mentioning
confidence: 94%
“…An example that supports this hypothesis is the observation that solid tumors (which are hyperproliferative, usually hypoxic, and highly dependent on glycolysis) re-express the fetal M 2 isozyme of PK in addition to an increased expression of all glycolytic enzymes and lactate dehydrogenase ( ). This phenomena has been particularly well-documented for human neuroectodermal (brain) tumors () and breast tumors ().…”
mentioning
confidence: 94%
“…Malignant cells have a high rate of aerobic glycolysis and biosynthesis. It has been suggested that the shift towards the M 2 isozyme in tumors represents a mechanism to gain allosteric control of the enzyme and allows for sequential activation and inhibition of the enzyme during the cell cycle [11,12]. Inhibition may occur so that the cellular concentration of glycolytic intermediates may be elevated transiently, enhancing glucose breakdown via the hexose monophosphate shunt and accelerating synthesis of pyrimidine and purine nucleotides in proliferating cells.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of phosphotyrosine detected after acid hydrolysis is small, not more than 507o of total phosphoamino acids, but was distinctly found in four different experiments. Tyrosine phosphorylation of PK seems not to be generally associated with cellular transformation as has been demonstrated by Rijksen et al [23]. M2-PK (or K4-type of PK) of medullary thyroid carcinomas of the rat contained phosphoserine and small amounts of phosphothreonine, but no phosphotyrosine was detectable.…”
Section: Resultsmentioning
confidence: 74%